Effect of manure, Phosphate Solubilizing Bacteria, and chemical fertilizer application on the growth and yield of soybean - HENNY KUNTYASTUTI; SUTRISNO SUTRISNO (Nusantara Bioscience, 2017)
Kuntyastuti H, Sutrisno. 2017. Effect of manure, Phosphate Solubilizing Bacteria, and chemical fertilizer application on the growth and yield of soybean. Nusantara Bioscience 9: 126-132. This study aimed to determine the dosages of organic, chemical and biological fertilizers for optimum growth and yield of soybean grown in acidic dryland. Treatments applied were twelve combinations of inorganic fertilizer, phosphate solubilizing bacteria (PSB), and manure. These treatments were arranged in a randomized block design, each was three replicates. The growth variables of plant height and chlorophyll index were observed in every two weeks interval, started at two weeks after planting. Root length and number of nodules were observed at 45 days after planting when the maximum vegetative growth occurred. Stem and root dry weight, number of filled and empty pods, pod dry weight, grain weight, and number of seeds per plant were observed at harvest. Optimum soybean growth and yield were achieved when soybean plants were treated with a combination of 1500 kg ha-1 of manure + PSB +150 kg ha-1 of NPK chemical fertilizer.